Development of Canva-Based E-Modules on Nanotechnology Materials for Class X High School Students - Iva Yuni Astuti; Isana Supiah Yosephine Louise (Jurnal Penelitian Pendidikan IPA, 2024)
The development of e-modules aims to be an effective learning resource for students. This research focuses on assessing the validity and student response to Canva-based e-modules on Nanotechnology material at the high school level. The research method used is Research and Development (R&D), using the Planning, Production, and Evaluation (PPE) development model. Data analysis was done quantitatively using descriptive techniques. The results showed that the e-module had been successfully made using the Canva application and had been validated by material experts, media experts, and educational practitioners, the validity of the product reached an average value of 94.4%, categorized as very good and declared feasible to be tested. Student response trials were conducted in two classes, namely small class trials reaching a score of 92.5 and large class trials with a score of 91.3. Both results fall into the very good category.